Comparison of retinal nerve fiber layer and macular thickness for discriminating primary open‐angle glaucoma and normal‐tension glaucoma using optical coherence tomography. (21st March 2016) - Khanal, Safal; Davey, Pinakin Gunvant; Racette, Lyne; Thapa, Madhu
Abstract: Purpose: The aim of this study was to evaluate the discrimination capabilities of macular and peripapillary retinal nerve fiber layer (pRNFL) thickness parameters as measured using spectral domain optical coherence tomography (SD‐OCT) between primary open‐angle glaucoma (POAG) and normal‐tension glaucoma (NTG). Methods: A total of 90 subjects were enrolled: 30 healthy subjects, 30 subjects with POAG and 30 subjects with NTG, consecutively. Retinal nerve fiber layer thickness, macular thickness and volume measurements were obtained with circular and radial SD‐OCT scans. All parameters were compared between groups using an analysis of variance test. Areas under receiver‐operating characteristic (AROC) curves with sensitivities at specificities greater than or equal to 90 per cent were generated to compare discrimination capabilities of various parameters between POAG and NTG. Results: Macular thickness and volume measurements were the highest in normal subjects, followed by NTG and POAG (p < 0.05). Average retinal nerve fiber layer thickness had perfect discrimination for normal‐POAG (AROC: 1.000; sensitivity: 100 per cent) and near perfect discrimination for normal‐NTG (AROC: 0.979; sensitivity: 93 per cent) as well as NTG‐POAG pairs (AROC: 0.900; sensitivity: 60 per cent). Inferior outer macular thickness (IOMT) and total volume were the best macular thickness and volume parameters having similar AROCs and sensitivities between normal and POAG (IOMT, AROC: 0.987; sensitivity: 92 per cent and total volume, AROC: 0.997; sensitivity: 97 per cent), normal and NTG (IOMT, AROC: 0.862, sensitivity: 47 per cent and total volume, AROC: 0.898, sensitivity: 67 per cent) and also between NTG and POAG (IOMT, AROC: 0.910, sensitivity: 53 per cent and total volume, AROC: 0.922, sensitivity: 77 per cent). In each comparison group, there was no statistically significant difference in AROCs between average retinal nerve fiber layer and inferior outer macular thickness, as well as total volume. Conclusions: The macular parameters offer comparable performance to pRNFL parameters for the discrimination of NTG and POAG. Average retinal nerve fiber layer thickness, total macular volume and inferior outer macular thickness were the best SD‐OCT parameters with superior discriminating capabilities.